PENERAPAN METODE MIND MAPPING PADA PEMBELAJARAN MATEMATIKA SIWA SMPN 48 SURABAYA - Nurdamayanti, Aulia (Buana Matematika : Jurnal Ilmiah Matematika dan Pendidikan Matematika, 2018)
This research is based on the frequent learning of mathematics which is generally centered on the teacher, which is often considered able to make the students can understand the material given. While, students should participate actively in learning, to be able to build ideas through the ability and thought in accordance with their understanding. This research is quantitative descriptive. The techniques used in this study are observation, questionnaires, and tests. Learning model in this research is using mind mapping method, because mind mapping method can help students to not always record writing as a whole. Students can present words, ideas, made on their own thoughts, understanding and creativity, and can understand the material for a longer period of time. Based on the background, the purpose of this research is to describe the student activity during the application of mind mapping method, to describe the student's response and the learning result after applying the mind mapping method on persamaan garis lurus. The conclusion that can be drawn from the application of mind mapping method on the equation of persamaan garis lurus of students of class VIII SMP Negeri 48 Surabaya is that with mind mapping method can make the students more active role in the class. And for learning outcomes also experience mastery at equation of equation.. Keywords: mind mapping, activity, response, learning outcomes